Can Antihypertensive Treatment Restore the Risk of Cardiovascular Disease to Ideal Levels?: The Coronary Artery Risk Development in Young Adults (CARDIA) Study and the Multi‐Ethnic Study of Atherosclerosis (MESA). Issue 9 (21st September 2015) - Liu, Kiang; Colangelo, Laura A.; Daviglus, Martha L.; Goff, David C.; Pletcher, Mark; Schreiner, Pamela J.; Sibley, Christopher T.; Burke, Gregory L.; Post, Wendy S.; Michos, Erin D.; Lloyd‐Jones, Donald M.
Abstract : Background: It is unclear whether antihypertensive treatment can restore cardiovascular disease risk to the risk level of persons with ideal blood pressure (BP) levels. Methods and Results: Data from the Multi‐Ethnic Study of Atherosclerosis (MESA) and the Coronary Artery Risk Development in Young Adults (CARDIA) study were analyzed. Outcomes were compared among participants without or with antihypertensive treatment at 3 BP levels: <120/<80 mm Hg, systolic BP 120 to 139 mm Hg or diastolic BP 80 to 89 mm Hg (120 to 129/≤80 mm Hg for participants with diabetes), and systolic BP ≥140 or diastolic BP ≥90 mm Hg (systolic BP ≥130 or diastolic BP ≥80 mm Hg for participants with diabetes). Among MESA participants aged ≥50 years at baseline, those with BP <120/<80 mm Hg on treatment had higher left ventricular mass index, prevalence of estimated glomerular filtration rate <60 mL/min per 1.73 m 2, prevalence of coronary calcium score >100, and twice the incident cardiovascular disease rate over 9.5 years of follow‐up than those with BP <120/<80 mm Hg without treatment. In CARDIA at year 25, persons with BP <120/<80 mm Hg with treatment had much longer exposure to higher BP and higher risk of end‐organ damage and subclinical atherosclerosis than those with BP <120/<80 mm Hg without treatment. An exploratory analysis suggested that when cumulative systolic BP was high (eg, >3000 mm Hg–years in 25 years), the increase in left ventricular mass index accelerated. Conclusions: The data suggest that based on the current approach, antihypertensive treatment cannot restore cardiovascular disease risk to ideal levels. Emphasis should be placed on primordial prevention of BP increases to further reduce cardiovascular disease morbidity and mortality.